Grooming Future Muslim Leaders At Permata Insan College With The Integration Of Naqli And Aqli Knowledge - Zakaria, Z.; Ahmad Hilmia, A.B.; Spawi, M. (Universiti Sains Islam Malaysia, 2024)
Leadership is one of the core values integrated in all subjects and co-curricular activities in PERMATA Insan College. Every gifted and talented student in the college is being groomed to be future Islamic leaders and scholars through the academic subjects, Quran and Sunnah studies, as well as co-curricular activities. Islamic Leadership is the component highlighted for students to develop and practise from early stage of life. This concept paper examines the implementation of an Islamic leadership development programme that encompasses every aspect of teaching and learning in PERMATA Insan College. It highlights the main principles and concepts of Islamic Leadership that have been integrated into the subjects and co-curricular activities as the college strive to develop the necessary leadership skills in every student. It would also discuss how the curriculum has been planned in such a way that it has the integration of Naqli and Aqli knowledge embedded into the curriculum and co-curricular activities.